Synthesis, Photophysics, and Potential Antifungal Activity of Benzo[a]phenoxazines - Bárbara S. G. Guimarães; Maria João Sousa; M. Sameiro T. Gonçalves (Chemistry Proceedings)
The synthesis and full characterization of new hydroxyl benzo[a]phenoxazinium chlorides with N-(di)propyl and/or N-isopropyl groups in the 5 and 9 positions are described. Photophysical studies carried out in ethanol and water revealed strong absorbances and significant fluorescence emissions at up to 676 nm. The antifungal activity was assessed against Saccharomyces cerevisiae and the results provide possible directions for further studies.